PENYULUHAN TENTANG HIV/AIDS PADA SISWA SMK KRISTEN 2 TOMOHON - Andro Ruben Runtu; Djoise Kaunang; Elizabeth Purba; Meilita Enggune; Welmin Lumi; Angelia Pondaa; Nolla Lolowang; Grace Merentek; Rivolta Musak; Ever Lontaan; Jeane Sumarauw; Agustinus Langitan (COVIT (Community Service of Tambusai), 2022)
To overcome the problem of the high incidence of HIV AIDS, the Republic of Indonesia Minister of Health Regulation Number 21 of 2013 concerning the prevention of HIV and AIDS has been stipulated, which contains efforts to overcome HIV/AIDS in Indonesia. So this activity is part of the community service carried out by AKPER Bethesda Tomohon lecturers, which aims to provide health education about HIV/AIDS to students at Christian Vocational School 2 Tomohon. There were 154 HIV/AIDS counseling participants, where this activity was an important part of efforts to prevent HIV/AIDS in the community, especially students. It is hoped that participants will benefit from this activity, such as knowing the HIV/AIDS disease process, causes, transmission, treatment and prevention. Participants were very enthusiastic about taking part in community service activities providing information about HIV/AIDS. Keywords: Counseling, HIV/AIDS